Second Church of Boston, 874 Beacon Street, n.d. - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking north from Audubon Circle of Second Church at the corner of Beacon Street and Park Drive. The parish house is the building to the right of the steeple. 9 9/16 x 7 9/16 overall 10 3/8 x 8 3/8 Photographs